Waste to wealth generation via areca plate manufacturing on micro scale - Adivappar, Nagrajappa; Sudeep, H.P.; Patil, Kirankumar R.; Swathi, H.C.; Revathi, R.M.; Ranjitha, P. (Journal of Plantation Crops, 2024)
Areca leaf sheath which was hitherto wasted on the garden has found profound importance in the hands of microenterprise owners. Value has been added to leaf sheath through their conversion into biodegradable plates and bowls. Micro scale production units are concentrated in arecanut hinterlands of Karnataka. The study was conducted considering 30 micro units from Shivamogga and Davangere districts of Karnataka. The average of total cost incurred, gross returns and net returns realized over the production period of six months was Rs. 315518.40, 4,21,000, 1,89,467 respectively. Profitability reflected in the Benefit Cost Ratio of 1.33 indicating that every rupee invested on plate manufacturing unit enabled manufacturer to reap gross returns of Rs. 1.67. Waste to wealth generation not only results in income generation but also results in employment generation for rural folk.